Effects of a large northern European no‐take zone on flatfish populationsa. Issue 4 (31st May 2013) - Florin, A.‐B.; Bergström, U.; Ustups, D.; Lundström, K.; Jonsson, P. R.
Abstract : In March 2006, a 360 km 2 no‐take zone (NTZ) was established north of Gotland in the central Baltic Sea, with the purpose to scientifically evaluate the effects of a fishing ban on flatfish populations. A monitoring programme was set up to study the populations in the NTZ and in a reference area east of Gotland where the fishing pressure was high. The programme included fishing with multimesh survey nets, modelling of potential larval export and estimation of fish consumption by large marine predators. Overall, the results showed a clear positive effect of the NTZ on turbot Scophthalmus maximus, with higher densities in the closed area compared with the fished area and also higher densities after closure compared with before. The NTZ also had older individuals and a more even sex ratio. This, in combination with a high potential for larval export from the NTZ to Gotland, shows that the marine reserve may be important for maintaining a viable S. maximus stock at Gotland. Also, for flounder Platichthys flesus, the densities were higher in the NTZ compared to the reference area and there was a net larval export to the fished area. For both species, density‐dependent growth was evident, with a lower length at age in the closed area. Potential predation by grey seal Halichoerus grypus and great cormorant Phalacrocorax carbo sinesis on flatfishes, that could hamper the evaluation of the marine reserve, was also addressed. Taken together, the results show that there are clear benefits of the fishing ban for both flatfish species within the NTZ, while the net effects on fisheries are difficult to quantify.